Simulación de rotores tipo savonius adaptando en sus alabes un perfil NACA (2020)
There are 3 main types of wind turbines, their difference lies mainly in their type of rotor, the direction of their axis, and the shape of their blades. For vertical axis, wind turbines are the Darrieus, Giromill, and Savonius. The present project, which aims to simulate the savonius rotor by adapting a NACA profile on its blades. For its execution there will be a CAD design software called SolidWorks® in which the geometry of the selected NACA profile will be outlined and generated to be used in the savonius rotor, after this and with the help of CFD simulation (Fluid Computational Dynamics) in the ANSYS software, its power coefficient is evaluated. Results were obtained from the comparison of the behavior of each rotor according to its power generated, power coefficient and speeds reached, showing that the adaptation of an aerodynamic profile improves the behavior of the rotor as the wind speed increases.